Targeting the Highly Vulnerable Households During Strict Lockdowns - Ducanes, Geoffrey (Archīum Ateneo, 2021)
In this brief article, we attempt to quantify the number of households in the country which are ‘highly vulnerable’ to hunger and poverty due to sudden and highly restrictive lockdowns, such as the enhanced community quarantine, and other social distancing measures, as well as estimate the budget that will be needed to address their vulnerability. ‘Highly vulnerable’ households are defined in this study as those unlikely to have incomes during strict lockdown periods because of the employment characteristics of their employed members and which likely have little or no savings to tide them over. Using nationally-representative household data, we define a job loss index to identify the employment characteristics that are most sensitive to the lockdown measures, and given these employment characteristics, identify the ‘highly vulnerable’ households. Depending on the pre-lockdown income threshold eligibility used, we estimate the number of ‘highly vulnerable’ households in the country at anywhere from 7.4 million to 11.3 million. At ₱5,000 per ‘highly vulnerable’ household, the estimated costs amount to ₱36.9 billion to ₱56.5 billion, again depending on the income threshold used. We also propose a way for the government to operationalize the process of identifying and helping ‘highly vulnerable’ households. JEL classification: I32, I38; H53